Constructing Colonial Benevolence: Portraits Of Persons With Leprosy In British Malaya - Por, Heong Hong (the Malaysian Branch of the Royal Asiatic Society Malaysian Branch of the Royal Asiatic Society, 2023)
Images of leprosy produced in British Malaya offer a way to explore connections between medical photography and colonial ideology. Using postcolonial history of medicine and critical visual studies, this article looks at the role of visual images in the formulation of colonial policy on leprosy. Viewing photos of leprosy against the background of colonialism, the politics of segregation, and the global migration of Chinese and Tamil labourers, I argue that medical photos of leprosy during British Malaya were not only objects of clinical significance but also a site of colonial representation of racial Others and pathogenic migrant bodies. As a critical engagement with historical photos, this article re-reads images of leprosy along and against the grain of colonial narratives to shed new light on colonial benevolence.